Magnetic field distribution due to shielding in a three-phase source - Said I.; Hussain H.B.; Kamaruddin M.N.A. (2023)
A three-phase, 415 V magnetic field source was developed using coils to represent magnetic field from a substation. Magnetic field was then attenuated using three different planar shielding materials placed above the coils. RMS magnetic fields were measured at the intersections of a 100 by 100 mm grid drawn on the shielding materials. Shielding effectiveness was evaluated at each measured point. The results were then plotted in linear and contour plots. It was found that for the same applied magnetic field, shielding effectiveness was not constant and varied with distance from source. At some areas on the fringes of the shielding material, the shielding effectiveness was found to be less than unity, indicating an increase in magnetic field, probably due to flux leakage and concentration of flux lines at those areas. Of the three materials used, silicon steel was found to have the best shielding property with shielding effectiveness of greater than 4.5 for applied magnetic field of 250 ?T. 2011 Asian Network for Scientific Information.